Cytokine and chemokine profile of the innate and adaptive immune response of schistosoma haematobium and plasmodium falciparum single and co-infected school-aged children from an endemic area of Lambaréné, Gabon - Ateba-Ngoa, Ulysse; Adegnika, Ayola Akim; Zinsou, Jeannot F; Kassa Kassa, Roland F; Smits, Hermelijn; Massinga-Loembe, Marguerite; Mordmüller, Benjamin; Kremsner, Peter G; Yazdanbakhsh, Maria (Malaria journal, 2015)
Helminths and malaria are among the most prevalent infectious diseases in the world. They both occur in tropical area where they often affect the same populations. There are studies suggesting an effect of helminths on malariometric indices. For example, malaria attacks as well as disease severity has been shown to be influenced by a concurrent chronic helminth infection. However, there are also studies that show no effect of concurrent helminth infections on malarial outcomes. To start addressing this issue, the effect of chronic Schistosoma haematobium infection on both the innate and adaptive immune response of Plasmodium falciparum-infected subjects was assessed in an area endemic for both these infections in Gabon. Subjects infected with S. haematobium and or P. falciparum, as well as a control group with neither of these infections, were recruited. For innate immune response, heparinized blood was obtained and cultured for 24 hours with a panel of TLR ligands. For adaptive immune response, PBMC was isolated and stimulated with SEB for 72 hours. Cytokines and chemokines were measured in supernatants using a multiplex beads array immunoassay. Principal Component analysis was used to assess pattern of cytokine and chemokine responses representing the innate and adaptive components of the immune system. Overall it was observed that the presence of P. falciparum infection was marked by an increase in innate and adaptive immune responsiveness while S. haematobium infection was characterized by an increased chemokine profile, with at the same time, lower pro inflammatory markers. When the study subjects were split into single infected and co-infected groups no effect of S. haematobium on the immune response of P. falciparum infected subjects was observed, neither for the innate nor for the adaptive component of the immune response. This study provides original information on the cellular immune response of S. haematobium and/or P. falciparum in infected subjects. It rules out an effect of S. haematobium on the cytokine profile of subjects co-infected with P. falciparum.